Association between pollinosis and obstructive sleep apnea hypopnea syndrome in the US population: evidence from the NHANES database 2005–2018 - Sen Zhang; Jianrui Pan; Tong Ge; Xueying Li; Lingling Ji; Run Liu; Zehui Gao; Hui Huangfu (BMC Pulmonary Medicine)
Abstract Background Rhinobyon and inflammation associated with pollinosis may elevate the risk of obstructive sleep apnea hypopnea syndrome (OSAHS). However, the exact nature of this association remains unclear, particularly in large-scale populations. This study aimed to examine the relationship between pollinosis and OSAHS using data from the National Health and Nutrition Examination Survey (NHANES). Methods Data from the NHANES spanning 2005 to 2018 were analyzed. Three multivariate generalized linear models (GLMs) were employed to explore the relationship between pollinosis and OSAHS: one unadjusted model, one minimally adjusted model, and one fully adjusted model. Stratified analyses were conducted to assess the impact of pollinosis and other covariates on OSAHS. Additionally, the study incorporated K-Nearest Neighbors (KNN) and smoothed curves to refine the analysis. Results The study identified significant demographic differences between groups in factors such as pollinosis, age, gender, weight (WT), body mass index (BMI), waist circumference (WC), protein, and fat. In three adjusted models, a consistent association was observed between pollinosis and OSAHS. Specifically, Model 1 showed an odds ratio (OR) of 1.31 [95% confidence interval (CI): 1.16–1.48, P < 0.001], Model 2 revealed an OR of 1.35 (95% CI: 1.19–1.54, P < 0.001), and Model 3 indicated an OR of 1.29 (95% CI: 1.10–1.50, P = 0.002), suggesting that the relationship between pollinosis and OSAHS remained robust despite the inclusion of other covariates. Risk stratification confirmed that pollinosis was a risk factor for OSAHS (OR = 1.28, 95% CI: 1.10–1.50, P = 0.002). The KNN model further supported the utility of pollinosis as a diagnostic marker for OSAHS. Smoothing curves also demonstrated a positive correlation between pollinosis prevalence and OSAHS incidence. Conclusion This study established pollinosis as a risk factor for OSAHS, emphasizing the need for vigilance in monitoring and managing OSAHS in individuals with pollinosis risk.